An investigation on factors affecting the internal audit effectiveness: A survey on the Libyan commercial banks - Aburabe, Hassan Musbah (2015)
The purpose of this study is to investigate the factors affecting an internal audit effectiveness (IAE) in the Libyan commercial banks. Therefore, this study employed a quantitative method through convenience sampling survey. To achieve objectives of the study, questionnaires were distributed online to 113 Libyan commercial banks. Eighty questionnaires were retrieved back from the internal auditors in the banks at the response rate of 70.8%. The data was analyzed through Statistical Package for Social Sciences (SPSS). The result showed direct relation effects of management support, organizational independence of internal auditors, competence of internal auditors and audit experience with the IAE within the Libyan commercial banks. According to the regression output, management support has significant and positive contribution for the IAE, while the other three variables: the organizational independence of internal auditors, competence of internal auditors and audit experience have shown positive relation with the IAE, however their contribution for the IAE are statistically insignificance. The whole four independent variables provide 52.8% of the contributions for IAE in the Libyan commercial banks. The variables have collective significance in identifying any non-compliance activities and could also add values for the IAE in the Libyan commercial banks